PENGARUH PENDIDIKAN, KOMPENSASI, BUDAYA ORGANISASI TERHADAP MOTIVASI KERJA KARYAWAN PADA PT. BANK RAKYAT INDONESIA.TBK KANTOR CABANG PARIAMAN - Octa Rosalinda; Sulastri Sulastri (Program Studi Magister Manajemen, 2016)
This study aimed to analyzethe influence of education, compensation, organizational culture on employee motivation at PT.BRI Branch Office Pariaman. Population in this study were all employees of organic and non-organic (contract employee) at PT.BRI Branch Office Pariaman. Sampling technique is proporsional cluster sampling. Sample were 110 people. Colected data were statistically analized with descriptive and inductive analysis consisting of multicollinearity test,normality test, heterocedasticity, linearity test and multiple regression analysis. Based on the result of this study concluded that (1) education have not a significant effect on employee motivation in PT. BRI Branch Office Pariaman.(2) Compensation significant effect on employee motivation at PT.BRI Branch Office Pariaman,(3) Organizational culture significantly influence employee motivation at PT.BRI Branch Office Pariaman.Keywords : Education, compensation, organizational culture, motivation